Systems of indicators and analysis of goals to increase the investment attractiveness of agricultural enterprises - Khatamov Ochildi Kurbanovich; Badalov Jamshid Jamolovich (THE INNOVATION ECONOMY, 2026)
The article examines the requirements for the system of indicators developed to assess the investment attractiveness of agriculture and the principles they must comply with. The article also analyzes a set of goals set at the regional, sectoral, and agricultural enterprise levels to enhance the investment attractiveness of the agro-indus trial complex